Free trade in the Americas - Morici, Peter (Twentieth Century Fund P. New YorkUS, 1994)
Examines the North American Free Trade Agreement between the United States, Mexico and Canada and looks at challenges of economic integration with a developing country undergoing radical reform viz. Mexico. Develops a strategy for building free trade in the Americas.